Hodnocení finanční situace vybrané obchodní korporace - Vozáková, Martina (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Bakalářská práce má za cíl za pomoci finanční analýzy zkoumat a hodnotit finanční situaci zvoleného podniku za období let 2011 až 2015 a také navrhnout řešení vedoucí k jejímu zlepšení. V práci jsou uvedeny veškeré potřebné informace sloužící k obeznámení se se zkoumaným podnikem, stejně jako teoretické poznatky a metody užívané ve finanční analýze. Dále následuje samotná analýza podniku opatřená komentáři.

The dissertation’s main goal is to research and evaluate the financial situation of the researched company from 2011 to 2015 with the help of the financial analysis, as well as suggest solutions leading to its improvement. In the thesis, there are stated facts and all necessary information used for better understanding of the exploring company with theoretical knowledge and methods used in the financial analysis. The next part contains actual analysis equipped with commentary.
Evaluation of the Financial Situation of the Selected Company
Keywords: finanční analýza; rozvaha; výkaz zisku a ztrát; cash flow; financial analysis; balance sheet; profit and loss statement; cash flow